Integrated bulk, single-cell and spatial transcriptomic analyses identify KIFC1 as a driver of malignant progression in lung adenocarcinoma - Linghan Tian; Yuanbiao Wang; Li Huang; Yuanyuan Meng; Wei Wu; Yu Cao; Zhenhua Ji; Zihan Wang; Jia Li; Xin Liu (Molecular Biology Reports, 2026)

Allelochemical-mediated bacterial homogenization and its potential role in mitigating chemical stress induced by plant invasion in alpine meadows - Xin Liu; Yaojun Ye; J. Aaron Hogan; Wenguang Sun; Minshu Song; Hang Sun; Yazhou Zhang (Applied Soil Ecology, 2026)

Identification and expression analysis of BAG gene family under salt and cold stress in soybean - Ping Sun; Zihan Kong; Xin Liu; Tiansheng Liu; Lina Jiang; Shimeng Xu; Hongli He; Zhiyao Dong; Xingzheng Zhang (Euphytica, 2026)

Correction: lnc-HOTAIR inhibits MTHFR expression to regulate endothelial cell proliferation and apoptosis in aSAH-induced cerebral vasospasm - Pingbo Wei; Dihong Chen; Yangyun Han; Qin Du; Le Luo; Chaohua Wang; Jiaxin Liu (Rendiconti Lincei. Scienze Fisiche e Naturali, 2026)

The impact of cumulative obesity and genetic susceptibility on biological aging in Chinese older adults - Jiening Yu; Liming Zhang; Zhenqing Yang; Xueqing Jia; Ciyun Zhao; Jiaxin Liu; Jingyun Zhang; Xingqi Cao; Yinyi Song; Lu Li; Xuehui Sun; Hui Zhang; et al. (GeroScience, 2026)

Cross-frequency SAR indices for rice mapping using multi-frequency and full-polarization data - Qihao Chen; Shuxin Liu; Guangchao Li; Ru Li; Yuanye Cao; Ge Su; Xiuguo Liu (International Journal of Remote Sensing, 2026)

Gomisin A Attenuates Cerebral Ischemia/Reperfusion Injury Through Activation of the VEGF/PI3K/AKT/NOS3 Signaling Pathway - Chenghe Zhao; Jiayue Yu; Kexin Liu; Shuangling Wang; Wenping Jing; Ziyi Zhao; Wenyue Zhuang (Cell Biochemistry and Biophysics, 2026)

Synergistic Effects of Biochar and Nitrogen Fertilizer on Soil Humification and Japonica Grain Yield in Black Soil Paddy Systems of Northeast China - Pingxin Liu; Haihang Sun; Jingwei Gao; Nan Wang; Shuai Wang (Journal of Soil Science and Plant Nutrition, 2026)

Retraction Note: Zinc Deficiency Causes Glomerulosclerosis and Renal Interstitial Fibrosis Through Oxidative Stress and Increased Lactate Metabolism in Rats - Zixuan Huang; Yajie Liao; Yunxi Zheng; Shang Ye; Qianyu Zhang; Xiaohong Yu; Xiaoxin Liu; Ningxu Li (Biological Trace Element Research, 2026)

Heavy metal pollution and associated health risk assessment in wild oysters from the Guangdong coast, China - Xiaomin Li; Xin’an Yue; Yaohui Chen; Jianping Ye; Zihua Zhou; Hong Qiu; Hua Wang; Jingxin Liu; Shengyong Li; Jinghuai Zhang (Marine Pollution Bulletin, 2026)

Soils sustainable management: How artificial humic acid reprogram bacterial consortia for enhanced humus synthesis - Xianghui Meng; Jiale Zhang; Jixin Liu; Yu Li; Xiaobin Wang; Shuang Ai; Jiayu Zhu; Zhuqing Liu; Fan Yang; Kui Cheng (Applied Soil Ecology, 2026)

Soil nitrogen loss reduces food web energy flow via nematode community simplification during wild fruit forest degradation in the Tianshan Mountains, China - Yulu Zhang; Dong Cui; Zhicheng Jiang; Haijun Yang; Zezheng Liu; Junqi Liu; Wenxin Liu; Yunhao Wu; Jinfeng Guo; Yaxin Han; Zhicong Zhang (Applied Soil Ecology, 2026)

Quantitative microbial element cycling reveals distinct functional characteristics associated with soil carbon and nitrogen cycling in clear-cut black locust plantations in winter - Kun Li; Yu Chen; Xiangcongcong Kong; Zhixin Rong; Jiaxin Liu; Ruiqiang Ni; Huimei Tian; Jiangbao Xia; Chuanrong Li; Qi Yao; Weixing Shen (Applied Soil Ecology, 2026)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

In Situ Biofilm Aquaculture Systems (In Situ BFSs ) for Litopenaeus vannamei : A Review - Wei Zhu; Guangnian Yuan; Zhiwen Song; Qiufen Li; Chao Liu; Ailing Xu; Yazhi Luan; Yongxin Liu (Reviews in Aquaculture, 2025)
The scale of intensive Litopenaeus vannamei aquaculture has increased over the past few decades. However, the inorganic nitrogen and suspended solids (SSs) generated during the aquaculture process are toxic to shrimp and have negative environmental effects. Therefore, removing these pollutants from aquaculture systems is a critical issue that must be addressed. In addition to the widely used recirculating aquaculture systems (RASs) and biofloc technology (BFTs), the addition of submerged substrates to L. vannamei aquaculture tanks to construct in situ biofilm aquaculture systems (in situ BFSs) is an alternative that results in favorable water quality and enables low or zero water exchange, significantly improving shrimp performance and decreasing the feed conversion ratio (FCR). This review highlights the principles, construction methods, water treatment effectiveness, and impact of in situ BFSs on L. vannamei growth as well as pathogen control. The selection of appropriate substrates and methods for nitrifying biofilm cultivation and substrate fixation can significantly affect water treatment efficiency, reduce the concentrations of harmful substances (SSs, ammonia and nitrite) and provide additional nutrients and habitats for L. vannamei , thereby increasing their survival rate and enhancing their growth performance. In addition, the integration of in situ BFSs with BFTs and algal‐symbiotic systems is discussed. In this paper, the potential for further increasing the treatment capacity of in situ BFSs through sulfur autotrophic denitrification (SAD) and electric field‐assisted biofilm systems is proposed. The application of these innovative technologies is expected to provide new insights and solutions for achieving sustainable development in L. vannamei aquaculture.

Computed tomography-based root structure variables determines root decomposition given a broad range of root and soil variables - Yingzhou Tang; JingWei Lian; Xuefei Cheng; Xin Liu; Hui Nie; Lei Wang; Dezong Sui; G. Geoff Wang; Jinchi Zhang; Lu Zhai (Applied Soil Ecology, 2025)

Contribution of microbial necromass to soil organic carbon and its influencing factors during plantation recovery in a subtropical rocky desertification region - Junjie Lei; Xiaoqian Gao; Ting He; Zongxin Liu; Wende Yan; Peng Dang (Applied Soil Ecology, 2025)

Effects of seed priming with different concentrations and forms of silicon on germination and growth of rice under cadmium stress - Yan Tan; Xin Liu; Zhibo Shen; Yang Xiao; Youjun Zhang; Huihui Du; Zhibin Wu; Dan Zhi; Avelino Núñez-Delgado; Yuan Yang (Applied Soil Ecology, 2025)